THE ANESTHESIA FEATURES UNDER ABDOMINAL BIRTH OF THE WOMEN WITH A TRANSPLANT KIDNEY - A. Yu. Korolev; A. V. Pyregov (Вестник анестезиологии и реаниматологии)
The article describes the medical cases of the successful abdominal birth of the women with a transplant kidney, linked with the available features in the intraoperative and postoperative periods. Such approaches as the combined walking epidural, the control of the transplant function and the assessment of the immunosuppressive therapy level were used with the anesthetic management of the intervention and the intensive therapy in the postoperative period.